PENERAPAN ASPEK RASIONALITAS DALAM PEMILU 2019 (STUDI TERHADAP TINGKAT PARTISIPASI POLITIK ODGJ DI KABUPATEN HULU SUNGAI UTARA) - Lesmana , Budi (Al Iidara Balad, 2019)
Election as a means of popular sovereignty is a vehicle for every citizen who has the right to choose to use his political rights and voice in choosing a leader. Without exception, based on the provisions in the legislation, every citizen can use this right.  In the implementation of the 2019 Election, the KPU strives maximally to accommodate all citizens who have the right to vote in the DPT. Repairs made many times are as an effort to increase voter involvement in elections.  One voter group that is a public concern and discourse is mental accessibility or more commonly referred to as People with Mental Disorder (ODGJ) who voted in the 2019 election. Outside the context that these mentally ill people are under forgiveness according to civil law, the constitution itself basically gives the same rights to people who have mental illness to choose. Even in the Election Law itself there is no prohibition explicitly governing this. This means that mentally ill people also have the right to exercise their right to vote. Not all mentally ill people have the awareness to choose. Of course, if there are certain conditions that are allowed to choose.  But how is the implementation of the business and rules in the field as an effort to increase voter participation by the organizers? And what is important is whether the application of direct, general, free, confidential and fair election principles can also be felt by ODGJ voters. Can their rights be used, but only choose formalities without secrecy. Don't let the voting rights of citizens with certain conditions be given an opportunity to commit fraud in the election. Fraud is detrimental to the voting rights of people who have mental disorders because it is considered easy to be cheated.